Protective Effect of Liriodendrin Isolated from Kalopanax pictus against Gastric Injury - Sohn, Yoon Ah; Hwang, Seon A; Lee, Sun Yi; Hwang, In Young; Kim, Sun Whoe; Kim, So Yeon; Moon, Aree; Lee, Yong Soo; Kim, Young Ho; Kang, Keum Jee; Jeong, Choon Sik (Biomolecules & therapeutics, 2015)
In this study, we investigated the inhibitory activities on gastritis and gastric ulcer using liriodendrin which is a constituent isolated from Kalopanax pictus. To elucidate its abilities to prevent gastric injury, we measured the quantity of prostaglandin E2 (PGE2) as the protective factor, and we assessed inhibition of activities related to excessive gastric acid be notorious for aggressive factor and inhibition of Helicobacter pylori (H. pylori) colonization known as a cause of chronic gastritis, gastric ulcer, and gastric cancer. Liriodendrin exhibited higher PGE2 level than rebamipide used as a positive control group at the dose of 500 μM. It was also exhibited acid-neutralizing capacity (10.3%) and H(+)/K(+)-ATPase inhibition of 42.6% (500 μM). In pylorus-ligated rats, liriodendrin showed lower volume of gastric juice (4.38 ± 2.14 ml), slightly higher pH (1.53 ± 0.41), and smaller total acid output (0.47 ± 0.3 mEq/4 hrs) than the control group. Furthermore liriodendrin inhibited colonization of H. pylori effectively. In vivo test, liriodendrin significantly inhibited both of HCl/EtOH-induced gastritis (46.9 %) and indomethacin-induced gastric ulcer (46.1%). From these results, we suggest that liriodendrin could be utilized for the treatment and/or protection of gastritis and gastric ulcer.